![please \: solve \: these \: questions please \: solve \: these \: questions](https://tex.z-dn.net/?f=please+%5C%3A+solve+%5C%3A+these+%5C%3A+questions)
Attachments:
![](https://hi-static.z-dn.net/files/da1/d6cae777b3cad17ee8247e3754c2e589.jpg)
Answers
Answered by
1
Answer:
hope it help u
Step-by-step explanation:
a)
Let, x = a-b , y = b-c , z = c - a
∴ x + y+ z = (a - b) + ( b - c) + (c - a) = 0
x + y = (a - b) + ( b - c) = a - c
y + z = (b - c) + ( c - a) = b - a
z + x = (c - a) + ( a - b) = c - b
Now,we know that ,
( x + y + z)³ = x³ + y³+ z³ + 3( x+y)(y+z)(z+x)
⇒0 =( a - b)³ + (b - c)³ + (c - a )³ + 3(a - c)(b-a)(c-b)
⇒(a - b)³ + (b - c)³ + (c - a)³ = -3 (a -c)( b - a)(c -b)
⇒(a - b)³ + (b - c)³ + (c - a)³ = 3(a -b )( b - c)(c - a)
∴Proved.
ask other ques by other images not all together
Similar questions